Explicit information on translation theory in contemporary Hungarian and English Bible prefaces – a contrastive approach - Tibor M. Pintér; М. Пінтер Тібор (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola, 2025)
Abstract. In this paper, an attempt will be made to present a kind of imprint of the translators’ metalinguistic activity by examining the preface of the most significant Hungarian Bible translations. This will involve an analysis of how they perceive their own translational and linguistic work, and how they evaluate their own linguistic work in the preface of the volumes. The summarised findings will then be synthesised with the relevant ideas concerning translation and language use, whilst acknowledging that recent studies have brought to light different concepts. The present study will primarily adopt a general linguistic perspective, with the possibility of incorporating a philological viewpoint, and will not utilise the tools of modern translation studies when analysing the texts. The analysis does not deal with the translation theories applied in the Hungarian Bible translations, but a more detailed knowledge of the content of the prefaces may help to gain a deeper understanding of the translation theories behind the translations. Research on the philological or linguistic topic of the prefaces of Bible translations is not new in the field, but an introductory sub-chapter of Christiane Nord’s study (Nord, 2016, pp. 568–569) is somewhat unique in that it employs seventeen English-language prefaces offered by BibleGateway in February 2016. The study’s conclusion asserts that despite the proliferation of 20th-century Bible translation theory and practice, English-language Bibles contain a paucity of information regarding the linguistic and grammatical aspects of translation, the purpose of translations, and strategies for the translation process. The research tries to determine what kind of linguistic information is relevant in the prefaces of Hungarian Bible translations. The aim of this study is to identify the metalinguistic information in the preface of the Bible translations, and to summarise the content relating to linguistic and translation studies: from early Hungarian translations from the 16–17th century, and from the current translations from the 20–21st century.

Резюме. У статті зроблено спробу представити своєрідний відбиток метамовної діяльності перекладачів шляхом аналізу передмов до найвизначніших угорських перекладів Біблії. Дослідження включає аналіз того, як перекладачі сприймають власну перекладацьку та мовну роботу, а також як вони оцінюють її у передмовах до видань. Узагальнені результати синтезовано з відповідними ідеями щодо перекладу та мововживання, з урахуванням того, що нещодавні дослідження висвітлили різні концепції. У даній праці переважає загальнолінгвістичний підхід, хоча можливе також залучення філологічної перспективи; при цьому не використовуються інструменти сучасного перекладознавства. Аналіз не стосується теорій перекладу, застосованих у зазначених угорських перекладах Біблії, проте детальніше ознайомлення зі змістом передмов може сприяти глибшому розумінню перекладацьких теорій, що лежать в основі цих перекладів. Дослідження філологічних або мовознавчих аспектів передмов до перекладів Біблії не є новим у цій галузі, однак підрозділ у вступі до дослідження Крістіане Норд (Nord, 2016, c. 568–569) є дещо унікальним, оскільки ґрунтується на аналізі сімнадцяти англомовних передмов, опублікованих на сайті BibleGateway у лютому 2016 року. У висновках дослідження зазначається, що, попри значне зростання теорії та практики біблійного перекладу у XX столітті, в англомовних Бібліях міститься вкрай мало інформації щодо мовних і граматичних аспектів перекладу, цілей перекладів та стратегій перекладацького процесу. Яка саме лінгвістична інформація є релевантною у передмовах до угорських біблійних перекладів? Метою цього дослідження є виявити метамовну інформацію в передмовах до перекладів Біблії та узагальнити зміст, пов’язаний із мовознавством і перекладознавством: як у ранніх угорських перекладах XVI–XVII століть, так і в сучасних перекладах XX–XXI століть.

A tanulmány célja, hogy bemutassa a fordítók metanyelvi tevékenységének lenyomatát a legjelentősebb magyar bibliafordítások előszavainak vizsgálatán keresztül. Ennek során elemzésre kerül, hogy a fordítók hogyan viszonyulnak saját fordítói és nyelvi munkájukhoz, valamint hogyan értékelik azt az egyes kötetek előszavaiban. A szintetizált megállapításokat ezután a fordítással és a nyelvhasználattal kapcsolatos releváns elméleti megközelítésekkel vetjük össze, figyelembe véve azt is, hogy a legújabb kutatások eltérő fogalmakat és nézőpontokat tártak fel. A vizsgálat elsősorban általános nyelvészeti nézőpontból közelít, esetlegesen filológiai szempontokat is integrálva, ugyanakkor nem alkalmazza a modern fordítástudomány módszertani eszközeit a szövegek elemzése során. Az elemzés nem foglalkozik a magyar nyelvű bibliafordítások fordítástudományi vonzatával, ugyanakkor az előszavak tartalmának részletesebb megismerése segíthet az egyes fordítások fordításelméleti hátterének mélyebb megismerésében. A bibliafordítások előszavainak filológiai vagy nyelvészeti vizsgálata nem új keletű a kutatások területén, azonban Christiane Nord tanulmányának egyik bevezető alfejezete (Nord, 2016, 568–569. o.) különlegesnek tekinthető abból a szempontból, hogy 2016 februárjában a BibleGateway által közzétett tizenhét angol nyelvű előszavat dolgoz fel. A tanulmány következtetése szerint, noha a 20. században a bibliafordítás elmélete és gyakorlata jelentősen kibővült, az angol nyelvű Bibliákban továbbra is kevés nyelvészeti és grammatikai információ található a fordítás nyelvi szempontjairól, céljáról és a fordítási stratégiákról. Arra a kérdésre keressük a választ, hogy milyen típusú nyelvi információ tekinthető relevánsnak a magyar bibliafordítások előszavaiban. A jelen tanulmány célja, hogy feltérképezze a bibliafordítások előszavaiban megjelenő metanyelvi információkat, és összefoglalja a nyelvészeti és fordítástudományi szempontból releváns tartalmakat a 16– 17. századi korai magyar fordításoktól kezdve a 20–21. századi jelenkori fordításokig.
Явна інформація про теорію перекладу в сучасних передмовах до угорських та англійських перекладів Біблії – контрастивний підхід
Fordításelméleti információk a kortárs magyar és angol bibliafordítások előszavaiban – kontrasztív megközelítés
https://aab-philologica.kmf.uz.ua/aabp
Keywords: Bible translations; translation studies; prefaces; source analysis; metalinguistic information